RETRACTED ARTICLE: Impact of rural tourism on residents’ well-being in traditional ancient villages: a case of North Guangxi - Xin Zhang (Heritage Science, 2021)
Abstract The impact of tourism on traditional Chinese villages is a topical issue; there are enough studies on this subject showing different views of the researchers. The recent trend towards cultural mutation and gradual disappearance of ancient traditions in rural areas is evident in developing countries. The study aims to examine the impact of rural tourism development on Chinese villagers’ welfare. The research data were collected in 2010 and 2020 by a survey method. Since the survey relies heavily on respondents’ perceptions, the survey results are somewhat subjective. However, the pretest–posttest study design partially solved this problem. Statistical processing was performed using the Student’s t-test; all data sets were checked for the normality of the distribution. The study concluded that there has been a significant socio-economic improvement in rural areas in the last decade (expansion of population’s purchasing power, enrichment of the cultural sphere), but despite this there is a tendency of migration from the villages to the cities, which is explained by gaps in regional policy.